The Chinese in Papua New Guinea (ANU Press, 2024)
Papua New Guinean, Chinese and Australian people have long been entangled in the creation of complex histories and political debates concerning the similarities and differences of each group. These debates are fundamental to understanding how a sense of national unity in Papua New Guinea is formed, as well as within analyses of the wider world of strategic power dynamics and influence. The Chinese in Papua New Guinea offers a comprehensive and nuanced examination of the Chinese in Papua New Guinea. Chinese, Papua New Guinean and Australian interactions are analysed in the context of ongoing shifts in colonial power, increased regional engagement with China, and current political instabilities across the Indo-Pacific region. The many ways the Chinese have been defined as actors in PNG's history and politics are analysed against the backdrop of a rapidly changing global order. The complexity of Chinese experiences within Papua New Guinea is given expression, here, with chapters that stress political and historical heterogeneity, the importance of language for understanding Chinese social relations, and that articulate rich personal experiences of race relations.